Salivary testosterone and cortisol measurement in sports medicine: a narrative review and user`s guide for researchers and practitioners - Hayes, L. D.; Sculthorpe, N.; Cunniffe, B.; Grace, F. (International Journal of Sports Medicine, 2016)
Since the initial reporting of salivary hormone measurements in marathon runners in the early 1980s, the practice of utilizing salivary testosterone (T) and cortisol (C) to reflect acute and rhythmic changes to their systemic counterparts has gained considerable momentum. However, substantial variability exists between studies with respect to methodological protocols, laboratory techniques, and interpretation of study findings. These differences can directly influence the salivary hormone values, thus hampering interpretation, limiting cross-study comparison, and constraining the generalizability of individual study findings. This article examines the current body of literature before proposing a sequence of practical guidelines to minimize sample variability in salivary hormone research. The guidelines are grouped into 3 major categories that limit comparison between studies; A) study design, B) sample acquisition and biological variation, and C) technical and analytical error. To achieve this, the present article critically appraises research employing salivary T and C measurements, identifies potential sources of error before proposing appropriate methodological considerations for researchers and practitioners wishing to obtain T and C measurement from saliva.